2023
DOI: 10.3390/healthcare11172371
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Tailored Dietary Education Program for Older Adult Patients on Hemodialysis: A Preliminary Study

Gayoung Park,
Seunghye Choi

Abstract: This study aimed to investigate the overall effects of a tailored dietary education program for older adult patients on hemodialysis (HD) based on self-efficacy theory, dietary knowledge and habits, nutritional intake, and biochemical parameters. A nonequivalent control group pre-test–post-test design was conducted for 8 weeks. The experimental and control groups received a weekly nutritional program and standard nursing care with an additional educational session, respectively. A clinical survey was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Table 1 shows the frequency and percentage-wise distribution of selected demographic variables among patients undergoing HD. Age distribution indicated a predominant presence in the 20 HD: hemodialysis.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Table 1 shows the frequency and percentage-wise distribution of selected demographic variables among patients undergoing HD. Age distribution indicated a predominant presence in the 20 HD: hemodialysis.…”
Section: Resultsmentioning
confidence: 94%
“…If the educational program focuses on dietary aspects for elderly HD patients, it will yield positive outcomes by enhancing their self-efficacy, elevating dietary knowledge, and fostering improved dietary habits and will reduce the intake levels of sodium, potassium, and phosphorus [ 20 ]. However, a descriptive, cross-sectional study conducted in Bloemfontein, South Africa, on the knowledge, attitude, and practices of patients receiving maintenance HD showed that nearly 50% of the HD patients had poor knowledge of dietary restrictions on renal diet, 60% had negative attitudes, and 61.4% had poor practice on diet adherence.…”
Section: Discussionmentioning
confidence: 99%